Global environmental sustainability trends: A temporal comparison using a new interval-based composite indicator - Irene Petrosillo; Erica Maria Lovello; Carlo Drago; Cosimo Magazzino; Donatella Valente (Environmental and Sustainability Indicators)
Assessing progress on the pursuit of the Sustainable Development Goals is crucial for evaluating the sustainability of a Country, although this is not easy, considering the interdependencies or interconnections of individual goals with others, and the fact that there are several indicators for each goal. The aims of this research are: (1) to propose a novel interval-based environmental sustainable composite index (ESI) suitable to monitor the worldwide environmental SDGs' implementation at national scale, (2) to solve the problem of missing data in large databases and the subjectivity in computing a composite index (CI), (3) to group and compare statistically countries according to the ESI, and (4) to represent spatially the results to identify areas of the world more or less environmentally sustainable than others. Clustering and Sankey diagrams have supported the temporal and spatial analysis of ESI trends, showing that Canada, Brazil, New Zealand, and several European countries have been the most sustainable in 2019. The novelty of this indicator is that each country presents an ESI central value, the most probable value of the composite indicator, and a range, which represents the uncertainty given by the lower and upper bounds. In this sense, it is possible to better interpret the results of the composite indicator, while simultaneously obtaining a measure of the uncertainty of the results. The composite indicator can be used to monitor countries’ vulnerability towards the unsustainability risk, as well as countries that are not able to escape from a sort of “unsustainability trap”.